THE RELATIONSHIP OF CARDIOVASCULAR RISK FACTORS AND ARTERIAL WALL STIFFNESS IN WOMEN WITH A HIGH ACTIVITY OF RHEUMATOID ARTHRITIS - D. S. Novikova; T. V. Popkova; A. N. Gerasimov; A. V. Volkov; E. L. Nasonov (Столичная издательская компания, 2015)
Aim. To study the relationship of arterial stiffness (determined by contour analysis of peripheral pulse wave) with cardiovascular risk factors in women with rheumatoid arthritis (RA). Material and methods. Women with high activity of RA (n=130) were examined. Women without rheumatic diseases (n=25) were included into control group. Assessment of the major traditional risk factors (TRF) of cardiovascular disease (CVD), duplex scanning of the common carotid arteries, transthoracic echocardiography (Echo-CG), and determination of serum inflammation marker levels were performed, in addition to evaluation of clinical symptoms, RA activity and severity. Indicators of digital pulse volume were determined by photoplethysmography. Results. Young and middle aged patients with RA after adjusting for the major TRF of CVD compared with women without RA have higher stiffness index (SI), reflecting increased stiffness of large arteries, and reflection index (RI), that shows raised tone of small arteries. The value SI>9.6 m/s or RI>70% is associated with a higher rate of diastolic dysfunction (DD), and left ventricular hypertrophy (LVH), while the more severe RA [high frequency III/IV radiographic stage, high levels of IgM rheumatoid factor (RF), anti-cyclic citrullinated peptide (anti-CCP)] and the history of inefficacy of tumor necrosis factor-α (TNF-α) inhibitors in the absence of significant differences in TRF of CVD. SI and RI values in patients treated with methotrexate were significantly lower than in patients receiving other basic anti-inflammatory drugs or not treated patients. Conclusion. Increased arterial stiffness that is associated with the development of DD and LVH, irreversible joint damages, higher IgM RF and anti-CCP levels may be one of the possible mechanisms of the relationship of RA severity and increased risk of cardiovascular complications. RI determination can be used for screening of LVH in women with RA of high activity.